Ethical basis of the International Financial Reporting Standards (IFRS) / Alami Youssef and Ouezzani Mohamed Rachid - Youssef, Alami; Mohamed Rachid, Ouezzani (Accounting Research Institute (ARI) & Faculty of Accountancy, 2015)
Similar to many other disciplines, accounting requires largely significant ethical knowledge and skills. Several studies have attempted to show the importance of ethics in the accounting profession. A popular issue is the accounting standards used by this profession, mainly the International Financial Reporting Standards (IFRS). Through a dialectical approach, we establish a content analysis of several articles of ethics' famous authors as well as the conceptual framework, IFRS content, and procedures used by the international accounting setter for the production and interpretation of standards. The results of this analysis enable us to identify the use of several principles, theories, and values of IFRS articulated by some authors and theorists of ethics. These international accounting standards are based on some theories of business ethics, particularly stakeholder and stockholder theories. Moreover, the IFRS use some ethical values of the capitalist society; such as equality, independence and security. These international accounting standards use several business ethics values, such as transparency, caution, confidence, respect, and honesty. Accordingly, several values and principles of ethics are implicitly present in the international financial and accounting standards.